Designing speaking interaction in LMOOCs: An eTandem approach. Issue 2 (10th May 2021) - Appel, Christine; Pujolà, Joan-Tomàs
Abstract: Promoting speaking interaction remains a challenge for language massive open online courses (LMOOCs), both from a pedagogical and technological standpoint. This paper describes the design process of the tandemMOOC, which exploits the massive, open and online features of MOOCs in order to offer language learners online speaking interaction practice with native speakers of their target language. The course is based on eTandem language learning principles and equips learners with the necessary competences to be able to cope with online second language (L2) speaking opportunities. Following a design-based research approach, this paper presents an analysis and discussion of seven components of the design: learning environment, facilitation dynamics, dyad configuration, task types, task topics, feedback provision, and gamification components. The analysis of the implementation of these elements results in a set of key features for the integration of L2 speaking interaction activities in LMOOCs.